Enterogastric reflux. Experimental model in rats. - Camejo, Marysol; Carlomagno, José L; Ramos, Leonardo; Rodríguez Domus, Julio; Fernández Naone, Gonzalo; Piñeyro, Alberto M (Cirugía del Uruguay, 2001)
An enterogastric reflux model was created in rats for the purpose of testing procedures for preventing reflux. This involved the study of the alterations brought about by enterogastric reflux on the gastric mucosa.